«TRANSFORMAR LA PIZARRA EN UNA PANTALLA BLANCA»: LINTERNAS MÁGICAS Y FANTASMAGORÍAS EN LOS INSTITUTOS ESPAÑOLES DEL SIGLO XIX - Daniel PITARCH, (Fonseca, Journal of Communication, 2023)
The first national network of public high schools in Spain was created in the mid nineteenth-century. Among the instruments for education that this institutions had, it is usually found a magic lantern. This paper shows what kind of lanterns and lantern slides were used in these collections and what could have been their use. This case study allow to focus on concrete practices of the history of the magic lantern and, in consequence, of the history of the audiovisual and its relation to education